SANITATION AND FAMILY ENVIRONMENTAL HEALTH STATUS AND ITS ASSOCIATION WITH STUNTING IN KULON PROGO, INDONESIA - Maria Theodora Natalia Hurint; Hendras Bintari; Yuliani Yuliani; Yulinda Kurniasari; Herwinda Kusuma Rahayu; Arif Sabta Aji (Ikatan Sarjana Gizi Indonesia (ISAGI), 2023)
Stunting remains prevalent in Indonesia. The indicators of the family's health were related with an unhealthy sanitation cause affect health and nutritional problems. This risk factor can affect the family to have stunting children. Objectives: The aim of this study was to analyze the relationship of family environmental sanitation status with stunting status in Kulon Progo. Methods: The Case-control study was conducted in 240 children with 80 cases (stunting) and 160 control (not stunting) groups, respectively. The subjects were 6-59 months and taken by purposive sampling technique in the public health center of Temon 2 in Kulon Progo, Indonesia. Stunting was assessed by z-score height for age which analyzed by WHO Anthro. Structured questionnaires were created to assess anthropometry, characteristics, and sanitation status in the household. A Chi-square test was used to analyze the data. Results: There was a relationship between family environment sanitation status and the incidence of stunting among subjects (p = 0.046; OR = 1.7; 95% CI = 1.01-2.99). Clean water availability in the households associated with the high risk of the children had stunting status (p = 0.012; OR = 2.1; 95% CI = 1.20-3.62). However, the other sanitation facilities such as a healthy latrine, trash can, and sewerage system had no association with the stunting risk in the household (p>0.05). Conclusion: This study found that if the families had not met the requirement of having clean water availability, they would have two times increase the risk of their children has stunting status.